An Efficient Distributed Scheduling Algorithm for Mobility Support in IEEE 802.15.4e DSME-Based Industrial Wireless Sensor Networks - Yun-Sung Lee; Sang-Hwa Chung (International Journal of Distributed Sensor Networks)
Recently, the Internet of Things technology has rapidly spread and been applied in various fields including smart factories. Smart factory technologies are used for flexible process automation and custom manufacturing; thus, it requires adaptive network management for frequent network fluctuations due to mobility. Moreover, it is very important to ensure the timeliness of the data collected through the sensor nodes. In order to ensure network mobility in industrial WSNs, distributed scheduling algorithms should be supported. In this paper, we evaluated IEEE 802.15.4e-based industrial WSN MAC performances by using various mobility scenarios for smart factory environments. Also we proposed an IEEE 802.15.4e DSME-based distributed scheduling algorithm for mobility support and measured various performance metrics. The proposed algorithm can adaptively assign communication slots by analyzing the network traffic of each node and improve the network reliability and timeliness. The experimental result shows that the throughput of DSME MAC protocol is better than IEEE 802.15.4e TSCH and legacy slotted CSMA/CA in large network with above 30 nodes. Also the proposed algorithm improves the throughput by 15% higher than other MACs including original DSME. The algorithm was experimentally confirmed to reduce power consumption by improving the availability of communication slots.